Fostering Narrative Writing Skills through Storyboarding: Evidence from High School Students - Arwin Tannuary; Arni Wulandari Sinaga; Yanti Kristina Sinaga; Sulistyani Sulistyani; Isry Laila Syathroh; Herman Herman (AL-ISHLAH: Jurnal Pendidikan, 2025)
Developing narrative writing skills remains a challenge for EFL learners, particularly in secondary education. This study investigated the effectiveness of storyboarding as an instructional medium to improve narrative writing among tenth-grade students at SMA Swasta Kampus Nommensen Pematangsiantar. A quasi-experimental design with non-equivalent control groups was employed. Forty students were purposively assigned to either an experimental group, which received instruction using storyboard-based activities, or a control group, which received conventional instruction. Narrative writing performance was measured before and after the intervention using a rubric assessing content, organization, vocabulary, grammar, and mechanics. Analysis of covariance (ANCOVA) was used to analyze posttest scores while controlling for pretest performance. The ANCOVA results indicated a statistically significant effect of storyboarding on narrative writing outcomes, F(1,37) = 24.57, p .001, partial η² = 0.40. Adjusted posttest means showed that students in the experimental group outperformed those in the control group (M = 78.3 vs. M = 67.9). The effect size was large, with Hedges’ g = 1.12, 95% CI [0.62, 1.62]. These findings suggest that integrating storyboards as visual-verbal planning tools significantly enhances students’ narrative writing, particularly in content development and organization. This study underscores the pedagogical value of interactive media in EFL writing instruction and recommends further research across diverse genres and educational contexts to generalize these results.